An analytical study to evaluate the impact of distributed zone fans on the air flow rate in a mechanical ventilation system. (July 2020) - Ju, Fa-Li; Liu, Liying; Yu, Xiaoping
Based on air flow rate testing of each branch fan in a distributed fan ventilation system under different branch air duct inlet static pressures, the conclusion can be drawn that there is a branch fan air flow rate deviation phenomenon. The air flow rate of the branch fan increases with the branch air duct inlet static pressure at the same branch fan speed, and the branch fan hinders the air flow rate in some cases. In this study, a theoretical expression of the deviation of the branch air duct design air flow rate was established, and the influencing factors of the deviation were determined to include the branch air duct resistance characteristics, branch fan performance, and branch air duct inlet pressure ratio. A graphic analytical method for determining the deviation of the branch fan design air flow rate was also proposed. Both methods can provide a theoretical basis for calculating and analysing the deviation of the branch fan design air flow rate in a distributed fan ventilation system. Practical application: This paper provides new data on the performance of a distributed fan ventilation system. Our results could be used to evaluate the impact of distributed zone fans on the air flow rate in a mechanical ventilation system. Crucially, we not only propose two types of methods that can be applied to predict deviations of the air flow rate in a distributed fan ventilation system caused by the branch air duct inlet static pressures but also obtain the factors that are important for understanding the true impact of the deviation of the branch fan air flow rate. This study lays an important foundation for the design and operation of building mechanical ventilation systems.